Prognostic Value of Pre-Treatment Prognostic Nutritional Index in Esophageal Cancer: A Systematic Review and Meta-Analysis - Hao, Jianqi; Chen, Cong; Wan, Fangfang; Zhu, Yuzhou; Jin, Hongyu; Zhou, Jian; Chen, Nan; Yang, Jing; Pu, Qiang (Frontiers in Oncology, 2020)
Abstract Background Prognostic nutritional index, combining albumin and lymphocyte counts, which represents the nutritional and immune status, was considered as a effective predictor for the patient's prognosis after surgery. To comprehensively analyze the relative effectiveness of prognostic performance of pretreatment prognostic nutritional index in esophageal cancer, we performed this meta-analysis. Methods We performed a systemic search in PubMed, EMBASE, CNKI and Web of science. The hazard ratios (HRs) or odds ratios (ORs) with their corresponding 95% confidence intervals (CIs) were extracted to explore the correlation between PNI and the postoperative survival of patients with esophageal cancer, including overall survival(OS), recurrence-free survival(RFS) and postoperative complications. The Newcastle-Ottawa Scale(NOS) was applied to estimate the quality of the included studies. The Begg's test was applied to assess the publication bias. Result A total of 13 articles with 3543 patients, were included in our meta-analysis, and 9 studies reported OS in 2731 esophageal cancer patients. The pooled results of the 9 studies suggested that esophageal cancer patients with a low prognostic nutritional index would have a worse overall survival(HR=1.14 95% CI 0.99-1.31 P<0.05). The integrated results also indicated that the prognostic nutritional index was a negative predictor for RFS. Conclusion This meta-analysis indicated a high correlation between PNI and postoperative survival of esophageal cancer. Esophageal cancer patients with low PNI value tend to have worse overall survival(OS) and may be at a higher risk of esophageal cancer recurrence. However, more relevant researches are needed to confirm the association between PNI and postoperative complications of esophageal cancer. Keywords: Prognostic nutritional index, Esophageal cancer, Prognosis, Meta-analysis, Overall survival